Multiple bladder calculi – a rare cause of overactive bladder complaints after pelvic organ prolapse operative treatment - Wlaźlak, Edyta; Surkont, Grzegorz; Dunicz-Sokolowska, Aldona; Wieszczycka, Maria; Sobieszkoda, Dominika; Stetkiewicz, Tomasz; Suzin, Jacek (Menopause Review/Przegląd Menopauzalny, 2007)
Multiple-vessel calculi in the setting of pelvic organ prolapse (POP is rare. It is easy to find it during ultrasound examination. The authors present a case where bladder ultrasound exam was not performed before complete uterine prolapse repair. On the fourth day after the operation the Foley catheter was removed. A few hours later in great urgency the patient delivered two calculi diameter 10 mm. Ultrasound exam showed multiple-vessel calculi. Before POP repair bladder ultrasound should be performed.